Public Debt and Government Guarantees - Same, Sinethemba (University of the Witwatersrand, Johannesburg, 2023)
The focus of this research paper is to examine the relationship between public debt and government guarantees. The analysis considers various macroeconomic indicators, including short-term and long-term interest rates, budget deficits and real GDP growth rate, as control variables. The study predominantly concentrates on 16 European countries, with South Africa being the only African country in consideration. The study employed Generalized Methods of Moments (GMM) which is a Dynamic Panel Data technique, and Fixed Effect in establishing this relationship. The study found a positive association between public debt and government guarantees, short-term real interest rate, and its lag as estimators using the Fixed Effect model. However, budget deficit, real GDP growth, and long-term interest rates exhibit a negative and significant relationship
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Finance & Investments to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2023
Keywords: Government Guarantees; Real interest rates; Budget Deficit; GDP growth rate; UCTD; SDG-8: Decent work and economic growth